Дворянин Великого князя - Святополк-Мирский Роберт Зиновьевич (На службе государевой, 2007)
Экземпляры: ф.2 (20191007) / Инвентарный номер: 51416 / Цена: 100.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 25 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6